HUSBANDS’ ATTITUDE OF CERVICAL CANCER EARLY DETECTION: IVA TEST - I Nova Alfiandhi; Yanti Hermayanti; Lilis Mamuroh (Journal of Maternity Care and Reproductive Health, 2020)
The increasing incidence of advanced cervical cancer is caused by the lack of women's participation in cancer early detection. One factor that may influence women to participate in early detection of cervical cancer through IVA test is the lack of husbands’ involvement, suggest, and support the wife to participate in cancer screening. The purpose of this study was to determine the husband's attitude about the IVA examination. This research method used quantitative descriptive, the sample in this study was 100 men, the sampling was chosen using the consecutive sampling method. Data was collected using a questionnaire about the husband's attitude and support. The research location was in Pasundan Public Health Center in Garut Regency. Data were analyzed using a univariant statistical test. The results of the analysis showed that most respondents, 87 people (87%) respondents did not support and only 13 people (13%) respondents supported the IVA test. The conclusions from this study show that most husbands do not support their wives who do VIA tests. Health education about IVA examinations to husbands and the socialization of the importance of wives to conduct IVA examinations would increase women's participation.Keywords: Attitude, Early Detection of Cervical Cancer, husbands, IVA Examination.